Analysis of Media Communication Systems Utilization for Natural Disaster Emergency Response Management in Reducing The Risk of Victims in Southeast Sulawesi - Sirajuddin; Hafied Cangara; Dadang A. Suriamihardja; Andi Alimuddin Unde (CV. Literasi Indonesia, 2022)
The purpose of this study is to analyze the significant contribution of communication systems in the form of information sharing (X1), collaboration (X2), and coordination (X3) through the use of media (Y1) to disaster management in Kendari and North Konawe Regency, Southeast Sulawesi Province. This research method uses a survey method with a quantitative research approach. In this study, the variables in question are information sharing (X1), collaboration (X2), coordination (X3) through the media (Y1). Sampling using a proportional sampling technique of 60 samples. Data collection techniques through questionnaires to respondents for primary data, while observation and interviews as complementary methods for data collection. The calculations for reliability testing are carried out through SPSS 25 computer program. The result of the study shows that The communication system for natural disaster emergency response in the form of information sharing (X1), collaboration (X2), coordination (X3) through the use of media (Y1) has a significant and robust effect simultaneously on disaster management in reducing the risk of victims in Kendari, and North Konawe Regency, Southeast Sulawesi Province.